International service learning assisting foreigners in learning croatian - Posavec, Kristina (Array, 2012)
This paper presents the conceptual framework for connecting interactive multimedia project AFILC (Assisting Foreigners in Learning Croatian) with the international service learning experience. Our main objective was to develop the system that will help international students at University of Zagreb to acquire the basics of Croatian language in a dynamic and interesting way, free of charge. Our second goal was to motivate foreign students to deeply experience another language and culture and to understand local customs by taking part in an international service learning course. Finally, our aim was to lay the foundations for structuring effective international service learning projects that will give foreign students insight into the relevance of their international and service experiences to their personal, career, educational and civic goals. At the same time, local students will get the opportunity to broaden the perspectives of their studies and to compare or contrast Croatian and international perspectives on the content of their study and civic education issues.